A multifarious comparative ecotoxicological approach on a catchment scale from three mine wastelands for improved environmental management and risk assessment: integrating abiotic, biotic and agroecosystem approaches - Mudenda, Lee (Department of Chemical Engineering, 2023)
Metal mobilization under acid or neutral rock drainage represents one of the major environmental impacts associated with mining of sulphidic minerals. To avert this, suitable handling of mine overburden material, waste rock, open pits and tailing storage facilities (TSF) is needed. This study addressed the risks associated with metal mobilization from the waste, including those resulting from the potential for ARD generation from the mine waste (tailings) following the recovery of copper from sulphidic ores, the impacts on the aquatic ecosystem, the agro-ecosystem and potential ecological restoration using phytomining technologies. The study is focused on the Kafue River basin on the Zambian Copperbelt and seeks to identify impacts and potential benefits through studying a grouping of TSFs and their impact in a single geographical region, allowing attributes of the facilities to be contrasted. In this study, we have addressed the categorisation of ARD generation of Chibuluma TSF, TSF15A and TSF14 tailing samples and associated metal mobility using the standard static tests, UCT biokinetic test and column bioleach experiments. Owing to the potential for compromised water quality and exploratory studies alluding to this, an ecotoxicology study at the catchment scale was conducted seasonally for three years on water resources (Nselaki Stream, Fikondo Stream and Mululu Streams) and food crops in close proximity to the selected TSFs. The potential of phytomining technologies using native herbaceous plants to mitigate mobilization of metals from the copper mine wastelands was investigated. Characterisation of the risk of ARD using data generated from the standard static and biokinetic tests was compared across the three samples. The biokinetic test supported the standard static test classification of non-acid forming, providing preliminary kinetic data on ARD generation. The three tailings have high neutralisation potential and are not acid forming over an initial period. Column bioleach tests allowed for differentiation of metals according to their leaching potential under conditions ranging from neutral through varying levels of acidity conditions, providing support evidence for potential ecological burdens. The results showed that low pH promoted significant release of Fe, Cu and Mn while release of metals Co, Ni, Zn and Pb remained considerably low. Low mobilization of metal species was observed under high pH, however, over time the sustained low mobilization of metal species is likely to cause significant ecological risks. The results better inform the risk posed by copper wastelands, through the combined use of a suit of tests (static, biokinetic and column leach tests). Under high acidic conditions, Fe and Cu exhibited high ecological risk while the risk was moderate under non-acidic conditions. The ecological risk under acidic conditions for Ca, Al, Mg and Mn was observed to vary from low to moderate, while negligible ecological risk profiles were observed with elements of interest Pb, Co, Zn, and Ni. Our research further expanded the studies on monitoring abiotic and biotic ecosystem drivers in adjacent streams. Selected physiochemical indicators downstream were identified in relation to the influence of the mine wastelands. No significant difference in heavy metals was observed between the three streams at the significance level (P > 0.05), however, notable changes in chemical and physical signatures for selected elements was reported downstream of the selected TSFs. Multivariate analysis such as principal component analysis, indicated prevalent TSF interferences of Cu, Co, Mn, Zn, and Pb in water and sediment samples analysed. The use of macroinvertebrates provided a useful approach to monitor the variation in the degree of impacts and characterise the ecological integrity of the streams, as well as evaluate the links with selected physiochemical contaminants. The various physiochemical markers used were useful in observing persistent impacts on macroinvertebrate taxa, which can be linked to severe anthropogenic impacts as well as timely warning indicators. Particularly, macroinvertebrate taxa tolerant to water pollution such as Talitridae and Gnathobdellidae were observed to be dominant species. The biotic monitoring results supported the abiotic test classification with regards to stream contamination. The use of macroinvertebrate community structures proved more useful to characterize the integrity of the ecosystem of the streams and determine the links with possible contaminants. Similarly, results from food crops irrigated using the selected streams reported significant elevation of metals Cu, Co, Mn, and Pb in the edible parts. The contamination load index (CLI) showed that the pollution index of Pb, at ≈43.8 in the vegetable samples, exceeded that of the other metals; equally, metal contamination was also determined in the edible vegetables for Cu, Co and Mn, but not consistently for Zn. One-way ANOVA at p≤0.05 and boxplot analysis suggests that heavy metal concentration in soils and crops did not vary significantly among the sites downstream of the TSF. In contrast, the soils in the upstream control sites showed much reduced metal content. These observations suggest that the TSFs may be the primary source of metal contamination in the selected streams. The study presents phytomining as an improvement approach towards mitigating the impacts of metal mobilization and rehabilitation of wastelands. Further, it acknowledges the benefit of vegetation of TSFs. A rich diversity of indigenous herbaceous plant species was observed to thrive on the low-grade wastelands, with 622 indigenous herbaceous species from 21 families and 46 genera identified. Through analysis of the rhizosphere and above- and belowground biomass of these plant species, the following plants reporting copper accumulation above 1000 ppm, terming them hyper-accumulators: A. eucomus, B. alata, C. floribunda, C. ductylon, C. alternifolius, H. filipendula, E. scuber and V. glabra. However, hyper-accumulation of Co, Zn and Mn was not observed despite accumulation to levels of 300, 200 and 1000 ppm respectively. Further, a number of the hyper-accumulators showed wide-spread acclimatisation to TSFs through their importance value index (IVI). Our findings suggest that phytomining using indigenous herbaceous plant species in Zambia has potential as a viable technology. Overall, the approach of comparing catchments impacted by similar land use activities, was observed to be valuable and useful in current and future management of watersheds exposed to similar challenges. The study highlights useful monitoring methods, key risks requiring mitigation and highlights the need for interventions. The comparative catchment scale study is unique and rare which few studies have utilised to assess the likely impacts of mine wastelands, while also investigating potential remedial measures.